SMARCB1-deficient poorly differentiated testicular carcinoma: a case report - Zhiying Wang; Zhixian Zhong; Yi Zhong; Cunya Li; Yun Li; Ling Xu; Shujuan Fu (Frontiers in Oncology)
In the present study, a 36-year-old male presented with left scrotal enlargement without an obvious cause, accompanied by a feeling of heaviness. Imaging examinations revealed a left testicular malignancy, the patient underwent left testicular mass removal,and the postoperative pathology results revealed a highly malignant germ cell tumor, with a tendency toward poorly differentiated embryonal carcinoma or seminoma. After surgery, the condition of the patient deteriorated rapidly, and distant tumor metastasis occurred. Lymph node puncture pathology results revealed poorly differentiated carcinoma consistent with SMARCB1/INI-1 deletion. Despite the use of chemotherapy, radiotherapy, immunotherapy and targeted therapy, the patient died 11 months after surgery. To the best of our knowledge, this is the first case report of a SMARCB1/INI1-deficient Poorly differentiated testicular carcinoma, which is very similar to testicular spermatocytic carcinoma in clinical diagnosis and deserves differentiation for future clinical diagnoses.This report provides important insights into the diagnosis and treatment of SMARCB1/INI1-deficient testicular malignancy. SMARCB1 is a crucial tumor suppressor gene, and its deficiency is closely associated with the development of various malignant tumors. The identification of this case suggests that future research should further explore the molecular mechanisms of SMARCB1-deficient tumors, particularly their role in testicular malignancies. Additionally, the diagnostic process of this case highlights that SMARCB1/INI1-deficient tumors can be clinically very similar to spermatocytic carcinoma of the testis, which can easily lead to misdiagnosis. Therefore, future clinical practice should emphasize the detection of SMARCB1/INI1 expression status, especially in the context of highly aggressive and rapidly progressing testicular malignancies, where immunohistochemical testing for SMARCB1/INI1 should be considered to confirm the diagnosis. In terms of treatment, this case demonstrates the highly aggressive nature and resistance to conventional therapies of SMARCB1/INI1-deficient tumors. Despite the patient receiving multiple treatments, disease progression could not be halted. This underscores the need for the development of novel therapeutic strategies targeting SMARCB1/INI1-deficient tumors, such as combinations of immune checkpoint inhibitors and targeted therapies, or other emerging immunotherapeutic approaches. Moreover, the treatment course of this patient also reflects the importance of individualized treatment plans. Future research should further explore precision medicine strategies based on tumor genetic profiles to improve patient survival rates and quality of life.